1994
DOI: 10.1111/j.1476-5381.1994.tb13108.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical administration of l‐arginine on formalin‐induced nociception in the mouse: a dual role of peripherally formed NO in pain modulation

Abstract: Japan 1 We investigated the effects of intraplantar (i.pl.) administration of L-arginine and N0-nitro-L-arginine methyl ester (L-NAME) on formalin-induced behavioural nociception in the mouse. 2 L-but not D-arginine, at 0.1-1 -g per paw, coadministered with i.pl. formalin, enhanced the secondbut not the first-phase nociceptive responses, whereas it was without significant effects at 3 fg per paw, and conversely, produced antinociception at 10 tLg per paw, resulting in a bell-shaped dose-response curve.3 L-NAME… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
73
2

Year Published

1996
1996
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(81 citation statements)
references
References 28 publications
6
73
2
Order By: Relevance
“…Furthermore, the antinociceptive action of MS was not associated with the increase of NO. These contradictions might be explained by considering that NO is a controversial molecule with dual effects, depending on its concentrations, NOS isoforms, redox balance, and the function of neuron subpopulations (Kawabata, 1994;Zhang et al, 2006). On one hand, increased NO production has been shown to produce antinociception (Bulutcu et al, 2002;Galdino et al, 2010;Garrido-Suárez et al, 2009;Granados-Soto et al, 1997;Sachs et al, 2004), on the other hand, NOS inhibitors elicit antinociception in some models of acute and persistent pain (De Alba et al, 2006;Milovanović et al, 2009;Yonehara et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the antinociceptive action of MS was not associated with the increase of NO. These contradictions might be explained by considering that NO is a controversial molecule with dual effects, depending on its concentrations, NOS isoforms, redox balance, and the function of neuron subpopulations (Kawabata, 1994;Zhang et al, 2006). On one hand, increased NO production has been shown to produce antinociception (Bulutcu et al, 2002;Galdino et al, 2010;Garrido-Suárez et al, 2009;Granados-Soto et al, 1997;Sachs et al, 2004), on the other hand, NOS inhibitors elicit antinociception in some models of acute and persistent pain (De Alba et al, 2006;Milovanović et al, 2009;Yonehara et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Others report that NO produces dual effects on nociception, depending on the dose and the pain model [6] . Although many studies have demonstrated that NO precursor L-Arg exerts dual effects on nociception [4,5] , the Ge et al [14] have reported that inhibition of spinal NO production contributes to the antinociceptive effect of emulsified isoflurane on formalin-induced pain. Kolesnikov et al [1] also report that supraspinal administration of the NOS inhibitor NOArg or oligodeoxynucleotide targeting the 4 nNOS isoforms can suppress the formalin response.…”
Section: Discussionmentioning
confidence: 99%
“…injection of L-arginine (L-Arg) can elicit antinociception in mice [3] . Another study suggests that NO plays dual roles in nociception in the brain or in the periphery [4,5] . Angela has reported that NO donor has dual effects on nociception, depending on the application dose and the pain model utilized [6] .…”
Section: Introductionmentioning
confidence: 99%
“…(10-100 mg/kg) as a pretreatment decreased formalin-induced hyperalgesia in the mouse paw in a dosedependent manner. Also, when L-NAME was co-administered with formalin intraplantarly [26] or given intrathecally (i.t.) before induction of infl ammation [27], dose-dependent antinociceptive activity was observed.…”
Section: Discussionmentioning
confidence: 99%